Removal of Bentazone Pesticide from Aqueous Solutions by Electro-oxidation Method - MOHAMMED AZEEZ OTHMAN (Salahaddin University-Erbil, 2021)
The kinetics of the electro-oxidation degradation of prepared aqueous solutions containing bentazone as a model compound of the thiadiazine group of pesticides was studied in the lab. The oxidation process was conducted under galvanostatic polarization in natural model media using boron-doped diamond (BDD) cathode and anode. Chemical oxygen demand (COD) estimation along the electro-oxidation treatment processing allowed the assessment of kinetic of organic compounds decay as well as the instantaneous current efficiency. The obtained data reflected that the degradation of bentazone pesticide is significantly dependent on initial amount of bentazone pesticide, current density and electrolytes concentration. COD removal follows a pseudo first-order kinetic and the electro-oxidation process was under the control of mass transport within the range studied, regardless the conditions of experimental. The COD removal rate increases with applied current density until 20 mA/cm2 and decreases for higher values. Two different concentrations supporting electrolyte (5mM, 10mM) were used. The rate of degradation increased significantly with increasing electrolyte concentration. The best obtained conditions for COD removal efficiency on the BDD electrode to degrade bentazone solutions (COD= 91.18 %) include operating at 20 mA/cm2 and 10 mM Na2SO4 as supporting electrolyte. This arrangement and condition allow to approximately complete degradation of bentazone in just 80 min. A decrease in the relative toxicity index value along the electro-oxidation indicate toxic compounds disappearance. The initial toxicity EC50 (5 min) and (15min) were decrease by 81% and 94%